Problematizing Disciplinarity, Transdisciplinary Problematics. (September 2015) - Osborne, Peter
This article situates current debates about transdisciplinarity within the deeper history of academic disciplinarity, in its difference from the notions of inter- and multi-disciplinarity. It offers a brief typology and history of established conceptions of transdisciplinarity within science and technology studies. It then goes on to raise the question of the conceptual structure of transdisciplinary generality in the humanities, with respect to the incorporation of the 19th- and 20th-century German and French philosophical traditions into the anglophone humanities, under the name of 'theory'. It identifies two distinct – dialectical and anti-dialectical, or dialectical and transversal – transdisciplinary trajectories. It locates the various contributions to the special issue of which it is the introduction within this conceptual field, drawing attention to the distinct contribution of the French debates about structuralism and its aftermath – those by Serres, Foucault, Derrida, Guattari and Latour, in particular. It concludes with an appendix on Foucault's place within current debates about disciplinarity and academic disciplines.